Principles of Macroeconomics - Greenlaw, Steven A.; Shapiro, David; Taylor, Timothy; Open Textbook Library (Open Textbook Library, 2017)
Principles of Macroeconomics 2e covers the scope and sequence of most introductory economics courses. The text includes many current examples, which are handled in a politically equitable way. The outcome is a balanced approach to the theory and application of economics concepts. The second edition has been thoroughly revised to increase clarity, update data and current event impacts, and incorporate the feedback from many reviewers and adopters. Changes made in Principles of Macroeconomics 2e are described in the preface and the transition guide to help instructors transition to the second edition. The first edition of Principles of Macroeconomics by OpenStax is available in web view here.
Chapter 1: Welcome to Economics! -- Chapter 2: Choice in a World of Scarcity -- Chapter 3: Demand and Supply -- Chapter 4: Labor and Financial Markets -- Chapter 5: Elasticity -- Chapter 6: The Macroeconomic Perspective -- Chapter 7: Economic Growth -- Chapter 8: Unemployment -- Chapter 9: Inflation -- Chapter 10: The International Trade and Capital Flows -- Chapter 11: The Aggregate Demand/Aggregate Supply Model -- Chapter 12: The Keynesian Perspective -- Chapter 13: The Neoclassical Perspective -- Chapter 14: Money and Banking -- Chapter 15: Monetary Policy and Bank Regulation -- Chapter 16: Exchange Rates and International Capital Flows -- Chapter 17: Government Budgets and Fiscal Policy -- Chapter 18: The Macroeconomic Impacts of Government Borrowing -- Chapter 19: Macroeconomic Policy Around the World -- Chapter 20: International Trade -- Chapter 21: Globalization and Protectionism
In English.
Description based on print resource
Keywords: Economics -- Textbooks